2018
DOI: 10.1371/journal.pone.0203659
|View full text |Cite
|
Sign up to set email alerts
|

Impaired hepatic amyloid-beta degradation in Alzheimer’s disease

Abstract: Extensive research strongly suggests that amyloid beta (Aβ) aggregates in the brain have a central role in Alzheimer’s disease (AD) pathogenesis. Pathological Aβ deposition is likely due to an altered balance between overproduction and elimination. Rodent studies have suggested that the liver has a major role in Aβ degradation. It is possible alterations of liver function could affect brain Aβ levels through changes in blood Aβ concentration. In this study, we hypothesized hepatic Aβ degradation to be impaired… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
53
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 28 publications
0
53
0
Order By: Relevance
“…A recent in vitro study using synthetic fluorescein-labelled A␤ 40 and A␤ 42 spiked into human liver homogenates has shown that A␤ degradation rates are lower in AD-derived homogenates as compared with those from non-demented control subjects, even after accounting for the covariates of age, sex, and APOE genotype. The authors conclude that their results "support the possibility that impaired hepatic A␤ degradation could be a factor contributing to increased brain A␤ accumulation and AD" [55]. In addition, serum-based bile acid metabolites are associated with AD biomarkers, providing further evidence that bile acid pathways play a role in AD pathophysiology [56].…”
Section: Clearancementioning
confidence: 89%
“…A recent in vitro study using synthetic fluorescein-labelled A␤ 40 and A␤ 42 spiked into human liver homogenates has shown that A␤ degradation rates are lower in AD-derived homogenates as compared with those from non-demented control subjects, even after accounting for the covariates of age, sex, and APOE genotype. The authors conclude that their results "support the possibility that impaired hepatic A␤ degradation could be a factor contributing to increased brain A␤ accumulation and AD" [55]. In addition, serum-based bile acid metabolites are associated with AD biomarkers, providing further evidence that bile acid pathways play a role in AD pathophysiology [56].…”
Section: Clearancementioning
confidence: 89%
“…We validate this finding in our study and also observed lower levels of phosphoinositols containing polyunsaturated fatty acids to correlate with poor Amyloid-beta clearance. An alternative explanation to our data is an impaired amyloid beta clearance in the liver(31)that subsequently leads to dysregulation of lipid metabolism in the liver. Overall, our data suggest that these lipid sets can serve as serum biomarkers for disturbed Amyloid beta pathway regulation in brain and can complement Amyloid beta imaging assays.…”
Section: Discussionmentioning
confidence: 57%
“…Both the kidney and liver are thought to be involved in the clearance of peripheral Aβ [88,89]. Liver function has been found to be inversely correlated with levels of peripheral Aβ in humans with and without AD [90,91], though current research does not indicate that peripheral levels are correlated with the Aβ1-40 and Aβ1-42 levels of the brain [90].…”
Section: Discussionmentioning
confidence: 65%